The Islamic Worldview as The Epistemological Foundation of Islamic Educational Philosophy - Negara, Achmad Husaen Sastra (Journal of Islamic Education and Ethics, 2026)
Existing studies on the epistemology of Islamic education frequently refer to the thought of Syed Muhammad Naquib al-Attas; however, many of them remain normative and fragmented, focusing primarily on moral education or the Islamization of knowledge without sufficiently articulating the Islamic worldview as a coherent epistemological foundation. This article aims to address this gap by conceptually reconstructing the Islamic worldview (ru’yat al-Islam li al-wujūd) as the ontological, epistemological, and axiological basis of Islamic educational philosophy. Employing qualitative library research and conceptual analysis of al-Attas’s major works, this study demonstrates that the Islamic worldview functions not merely as a theological framework but as an integrated epistemological structure that determines the nature of knowledge, truth, and educational purpose. The findings revealed that positioning the Islamic worldview as an epistemological foundation enables Islamic education to overcome relativism, secularization, and the dichotomy of knowledge, while reorienting education toward the formation of civilized human beings (ta’dīb). The theoretical contribution of this study lies in clarifying the epistemological role of the Islamic worldview in Islamic educational philosophy and in offering a conceptual framework to guide curriculum development, learning practices, and educational objectives in contemporary Islamic education.